Alpha-1 antitrypsin deficiency is significantly associated with atopy in asthmatic patients. (2nd January 2022) - Aiello, M.; Frizzelli, A.; Pisi, R.; Fantin, A.; Ghirardini, M.; Marchi, L.; Ferrarotti, I.; Bertorelli, G.; Percesepe, A.; Chetta, A.
Abstract: Background : Although the etiology and disease mechanisms of asthma and alpha-1 antitrypsin deficiency (AATD) are distinct, several reports indicate that asthma is common in AATD patients, however the relationships between asthma and AATD are poorly described in the literature. Objectives : The aim of the study was to investigate in a cohort of outpatients affected by mild to moderate asthma the clinical features that may differentiate asthmatic patients with and without mutation on SERPINA1 gene. Methods : Seven hundred thirty-five asthmatic outpatients underwent quantitative analysis of the serum level of alpha-1antitrypsin. According to the literature only sixty-seven out of seven hundred thirty-five asthmatic patients were submitted to genetic analysis to identify AATD and non-AATD subjects. Fifty-eight patients were studied. Clinical and functional data, including lung function, atopy and bronchial hyperactivity, were recorded. Results : The fifty-eight asthmatic patients were divided in AATD patients ( n = 22) and non AATD patients ( n = 36), according to genotype. The presence of atopy was significantly higher in patients with AATD than in those without AATD (91% vs. 64%; p = 0.031). AATD patients reported allergic manifestations more than non AATD patients (77% vs. 47%; p = 0.030). Conclusion : Our study shows that the presence of atopy in asthmatic patients with AATD is significantly higher than in asthmatic patients without gene mutation. In addition, a higher percentage of AATD patients self-reported allergic manifestations. No significant differences in respiratory symptoms, physical examination, disease severity or inflammation markers were found between AATD patients and non AATD patients.